MENINGKATKAN KESADARAN MAHASISWA UNIVERSITAS INTERNASIONAL BATAM MENGENAI PENTINGNYA MONEY MANAGEMENT DAN INVESTASI - Isnaini Nuzula; Ardila Ardila; Shellyna Shellyna; Feby Fitria Salim; Shieny Tan Putri; Zulfiniar Nur Karimah; Rama Aryobimo; Yohana Yohana (National Conference for Community Service Project (NaCosPro), 2020)
Until now the COVID-19 pandemic has not subsided and has had a huge impact on the world economic conditions. One of the community groups affected by this condition is the college students in Universitas Internasional Batam, whereas most of the students are self – financing for their studies. The main objective of this community service activity is to increase the understanding of UIB students about money management and investment through infographics which contain information to be conveyed so that students can easily understand. This activity was divided into three stages, namely extracting initial information about the level of knowledge of UIB students regarding money management, designing infographics, and finally distributing and disseminating the resulted infographics. By using infographics, hopefully, could help students in managing finances so they can avoid financial problems and know the importance of providing emergency funds that can be saved in the form of investments because the investment is also one way to get additional income. The infographic has been socialized through social media, especially in some webpages related to Universitas Internasional Batam. Based on a poll conducted on students who have read the infographic, 92% of them said this infographic was useful, and it could increase their understanding of money management and investment.